Peran Gereja dalam Pembinaan Iman terhadap Masyarakat Tertekan - Evimawati Harefa; Antonius P Sipahutar; Mesradiayanti Hulu (Journal New Light, 2025)
This writing departs from the author’s concern about the realities that often occur in the development of faith in communities that experience pressure. In a situation where society faces various pressures and challenges, faith formation becomes increasingly important to maintain the spirituality strength of individuals and communities. The author’s concern about this condition encourages him to highlight the need for attention and concrete efforts in strengthening the faith of people who are threatened by external and internal factors. This writing aims to stimulate reflection and concrete action in strengthening individual and community faith. The method used in this thesis is a literature review, which is expected to provide a strong foundation for developing effective and relevant faith formation strategies for communities experiencing pressure. Through this writing, the author hopes to create awareness of the importance of paying special attention to faith formation in communities experiencing pressure. By strengthening faith and spirituality, it is hoped that people can find calm in facing the various challenges they face. Therefore, cultivating the faith of depressed communities ia an important task and responsibility for the Church week end pastoral a spirituality institution. By providing appropriate support, guidance and spirituality formation, The Church can be a source of strength and hope. Thus the Church has an important role in helping society to overcome the various challenges it faces.